Breath-Holding Spells: Etiopathogenesis, Clinical Features, and Treatment Principles - Kodirberdi ugli, Anorboyev Sardor (Research Journal of Trauma and Disability Studies, 2025)
Breath holding spells are a common and potentially serious non-epileptic paroxysmal event in childhood, characterized by sudden cessation of breathing, changes in skin color, and sometimes brief loss of consciousness. This condition is usually triggered by emotional stress, fear, or pain, and causes significant anxiety in parents. Although these paroxysms are considered benign, they can have a significant impact on the child's health and family life. This article provides a scientific review of the pathophysiology, clinical manifestations, and current treatment options for breath holding spells.